The Effect of Pelvic Rocking with a Birth Ball on the Progress of Labor During the Active Phase of the First Stage of Labor - Nining Sulistyowati; Ani Mulyandari (PT Inovasi Pratama Internasional, 2026)
Prolonged labor can lead to increased morbidity and mortality rates in both mothers and infants. Therefore, measures must be taken to prevent prolonged labor, one of which is the use of the nonpharmacological “Pelvic Rocking” technique with a birth ball, which can facilitate labor progress and accelerate the process. This study aims to analyze the effects of pelvic rocking using a birth ball on labor progression during the active phase of the first stage of labor. The method applied in this study is a quasi-experimental design with a posttest-only control group. The study population consisted of all mothers in labor at the TPMB in Tanjungpinang City, with a sample size of 34 mothers in the active phase of the first stage of labor, divided into two groups (intervention and control). Consecutive sampling was used, while data analysis was performed using the Mann-Whitney U test. The findings of this study indicate that the pelvic rocking method using a birth ball did not have a significant effect on the progress of labor during the active phase of the first stage of labor, with a p-value of 0.086 (>0.05). Based on these results, it can be concluded that the pelvic rocking method using a birth ball can serve as an effective strategy to accelerate the labor process, provided that supporting factors are taken into account.